Credit Risk Analysis on Motor Vehicle Financing Using the Kealhofer Merton Vasicek Model (KMV) - Rambe, Dwi Wahyuni; Rakhmawati, Fibri (Information Technology and Science (ITScience), 2025)
The development of the automotive sector in Indonesia continues to show significant growth, in line with the increasing demand for motor vehicles, both cars and motorcycles. Although it has great potential, the vehicle financing sector is not without challenges, particularly related to credit risk. The Kealhofer Merton Vasicek (KMV) model will be suitable for calculating vehicle credit risk because it can predict default (failure to pay) when the borrower reaches the end of the loan term. The objective of this research is to apply the KMV model to calculate the Expected Default Frequency (EDF) value and determine the minimum credit risk. From the analysis and estimation results, the time-to-maturity equity value for motor vehicles was obtained at Rp9.616.709.886 and the time-to-maturity liability value at Rp1.865.460.114, while for cars, the equity value was obtained at Rp2.057.843.305 and the time-to-maturity liability value at Rp468.544.695. Additionally, the Expected Default Frequency (EDF) value for motor vehicles was obtained at 4,26% and the EDF value for cars at 0,01%. The results indicate that the likelihood of default experienced by Adira Finance is low, especially for cars. Therefore, Adira Finance can be stated to have sufficient capital, so the likelihood of default is not high.